Cardiac Children Hospital Early Warning ScoreVersus the Inadequate Oxygen Delivery Index for the Detection of Early Warning Signs of Deterioration. (23rd January 2023) - Khalil, Mujtaba; Abbas, Qalab; Azhar, Mohammad Kumael; Aamir, Faiqa Binte; Hashmi, Shiraz; Ali, Sadaqat; Faiz, Tahira; Malik, Mahim Akmal
Abstract : OBJECTIVES: To assess the utility of the Cardiac Children's Hospital Early Warning Score (C-CHEWS) in the early detection of deterioration. DESIGN: Single-center longitudinal pilot study. SETTING: Pediatric cardiac ICU (PCICU), Aga Khan University. INTERVENTIONS: C-CHEWS and Inadequate Oxygen Delivery (IDO2 ) Index calculation every 2 hours. PATIENTS: A total of 60 children (0 d to 18 yr old). MEASUREMENTS AND MAIN RESULTS: A single-center longitudinal pilot study was conducted at PCICU. All postoperative extubated patients were assessed and scored between 0 and 11, and these scores were then correlated with the IDO2 index data available from the T3 platform. Adverse events were defined as a need for cardiopulmonary resuscitation, or reintubation, and death. A total of 920 C-CHEWS and IDO2 scores were analyzed on 60 patients during the study period. There were 36 males and 24 females, and the median age of the study population was 34 months (interquartile range, 9.0–72.0 mo). Fourteen patients (23.3%) developed adverse events; these included 9 reintubations and 5 cardiopulmonary arrests, resulting in 2 deaths. The area under the curve (AUC) for C-CHEWS scores fell in an acceptable range of 0.956 (95% CI, 0.869–0.992), suggesting an optimal accuracy for identifying early warning signs of cardiopulmonary arrest. Whereas, IDO2 showed no discriminatory power to detect the adverse events with an AUC of 0.522 (95% CI, 0.389–0.652). CONCLUSIONS: The C-CHEWS tool provides a standardized assessment and approach to deteriorating congenital cardiac surgery patients in recognizing early postoperative deterioration.